2014
DOI: 10.1007/s00013-014-0714-5
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for univalence and quasiconformal extension of harmonic mappings in terms of the Schwarzian derivative

Abstract: Abstract. We prove that if the Schwarzian norm of a given complex-valued locally univalent harmonic mapping f in the unit disk is small enough, then f is, indeed, globally univalent and can be extended to a quasiconformal mapping in the extended complex plane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…The proof of the univalence criterion in Theorem 1 follows closely the reasoning in [12]: We show that if a harmonic mapping f = h + g has small Schwarzian derivative then so does its analytic part h, and therefore h is univalent by Theorem A. The same can then be said about h + ag, the analytic part of the affine transformation f + af , a ∈ D. Finally, Hurwitz' theorem shows that h + ag is univalent for every a ∈ D and by an elementary rotational argument we get that f is injective.…”
Section: Harmonic Mappingsmentioning
confidence: 79%
See 1 more Smart Citation
“…The proof of the univalence criterion in Theorem 1 follows closely the reasoning in [12]: We show that if a harmonic mapping f = h + g has small Schwarzian derivative then so does its analytic part h, and therefore h is univalent by Theorem A. The same can then be said about h + ag, the analytic part of the affine transformation f + af , a ∈ D. Finally, Hurwitz' theorem shows that h + ag is univalent for every a ∈ D and by an elementary rotational argument we get that f is injective.…”
Section: Harmonic Mappingsmentioning
confidence: 79%
“…This shows that if σ H (Ω) > 0 and Ω is finitely connected then, in view of Theorem B, every boundary component of Ω is either a point or a quasicircle. For Ω = D it was shown in [12] that σ H (D) > 0. We prove that the harmonic inner radius is positive for all quasidisks.…”
Section: Harmonic Mappingsmentioning
confidence: 98%
“…The argument of the proof is analogous to the one used to prove Theorem 1. Condition (11) implies that there exist a real number ρ with 1/2 < ρ < 1 and ε > 0 such that (12) |S…”
Section: The Cauchy and Poisson Integral Formulas Now Givementioning
confidence: 99%
“…In particular, the authors of [5] observed a deep connection of S f with lifts of harmonic functions onto minimal surfaces. In [15,16] some estimations of S f in some subclasses of univalent harmonic functions were obtained and many properties of the Schwarzian were established. Norms of the Pre-Schrarzian and Schwarzian derivative S f were estimated in [14] for the linear-and affine-invariant families of harmonic functions in terms of order of the family; so, analogues of the Krauss and Nehari theorem about the upper bounds of |S f | were obtained.…”
Section: S[h](z)| ≤ 2p(|z|) In Dmentioning
confidence: 99%
“…In [16] R. Hernández and M. J. Martín proved an analogue of Theorem A for the S f in the following form: they proved the existence of constant C such that for f = h + g the inequality…”
Section: S[h](z)| ≤ 2p(|z|) In Dmentioning
confidence: 99%